An Analysis of Translation Ideologies on Andmesh Indonesian Song “Hanya Rindu” into English “Just Missing You” Emma Heesters - Desi.A.R. Simbolon; Susi Santrika Sitinjak; Yesica Hageltira Sitorus; Laminton Sihotang (Journal of Language Education (JoLE), 2025)
This study analyzes the translation ideology behind the English rendition of the Indonesian song "Hanya Rindu" by Andmesh Kamaleng, performed by Emma Heesters as "Just Missing You". Using Lawrence Venuti's framework of domestication and foreignization. the research investigates how ideological choices influence the emotional and cultural conveyance of song lyrics across languages Employing a qualitative descriptive method, twelve lyrical segments were examined to identify translation strategies and ideological tendencies. The results show a dominant use of domestication (58.3%), where the lyrics are adapted for emotional relatability and fluency in English, using strategies like modulation and adaptation Foreignization (41 7%) appears in instances preserving cultural elements, such as religious references and familial terms. The translator's use of five main strategies literal translation, modulation, adaptation, transposition, and reduction-demonstrates a flexible, nuanced approach to lyric translation. This study concludes that the English version reflects a balance between cultural fidelity and accessibility, contributing to a deeper understanding of translation ideologies in the